Evaluation of different field treatments on seed and seedling quality of onion against purple blotch disease: Effect on purple blotch of onion (Bangladesh Journal of Agriculture, 2023)
An investigation was carried out at Sher-e-Bangla Agricultural University, Dhaka, Bangladesh to evaluate the effect of some field treatments' on seed and seedling quality of onion. From the 16 treatment integrations, the harvested seeds were significantly varied in terms of seed germination, seedling vigor, Zinc & Boron content, and the presence of pathogenic microorganism in onion seed. Treatment T11 (Score 250 EC+Poultry waste) and T8 (Rovral+Poultry waste) showed significantly the highest seed germination of 99.50%, 99% and vigor index of 1592 & 1438; respectively. The Zn and B contents in seed were found to be increased in the seed produced from the integrated treatment where micronutrient was applied. The T9 treatment (Rovral + Zn+B) and T12 (Score 250 EC + Zn+B) showed the best result in respect of Zn and B contents. No pathogenic microorganisms were found in treatment T11 (Score 250 EC+Poultry waste) and T8 (Rovral+Poultry waste) which was statistically significant over T1 (Rovral 50 WP), T2 (Score 250 EC), T3 (Alamanda), T7 (Rovral + Bioagent) and T9 (Rovral + Zn+B).Bangladesh J. Agri. 2023, 48(1): 40-50